Capacity strengthening of village health volunteers during and post-COVID-19: a model to prepare for emerging diseases - Nawan, Punnatorn; Raksilp, Monthicha; Kankarn, Waratip; Songserm, Nopparat (Intelektual Pustaka Media Utama, 2025)
Village health volunteers (VHVs) were essential in handling during and post-coronavirus disease 2019 (COVID-19). This study aimed to develop the capacity enhancement model of VHVs in preventing COVID-19 in Thailand. The development process and data collection used 12 stakeholders and 55 VHVs, respectively. The research tools were focus group discussions and questionnaires. We employed descriptive and inferential statistics for quantitative and content analysis for qualitative data. The model development was implemented in 9 processes: i) study the situation, ii) brainstorm to analyze the problems, iii) set the guidelines for model development, iv) organize training, v) review of role-based skills, vi) conduct public relations, vii) observe and follow up, viii) evaluate the operation, and ix) reflect on the results and lessons learned. After the model was developed, knowledge, attitude, and behavior in preventing COVID-19 were significantly better than before their capacity was enhanced (p<0.001). The model named “NAMKHUN Model,” which consisted of N=working as a network; A=ability to use application; M=effective management; K=up-to-date knowledge; H=having health literacy; U=having unity; and N=fast, accurate and up-to-date News). The success factor from the lesson learned was teamwork, which complements up-to-date knowledge and will create desirable skills for dealing with emerging diseases in the future.